Environmental and economic impacts of different sugarcane production systems in the ethanol biorefinery - Chagas, Mateus F.; Bordonal, Ricardo O. [UNESP]; Cavalett, Otavio; Carvalho, Joao Luis N.; Bonomi, Antonio; La Scala, Newton [UNESP] (Wiley-Blackwell, 2016)
Economic and environmental impacts of ethanol biorefineries with different sugarcane (Saccharum spp.) production technologies are evaluated with a focus on harvesting systems, reduced tillage, controlled traffic farming to reduce soil compaction, and alternatives of sugarcane rotation. Results showed that scenarios with sunn hemp (Crotolaria juncea) as a rotation crop in the sugarcane cycle present great potential to decrease environmental impacts of sugarcane biorefineries. Although reduced tillage promotes a reduction in sugarcane production costs in comparison to conventional tillage, it only cause a slightly decrease (less than 5%) on ethanol environmental impacts. Use of soybean (Glycine max) as a rotation crop yields an extra source of income, increasing the net agricultural revenues by 15% compared to scenario with sunn hemp. However, better economic and environmental impacts for sugarcane biorefinery are obtained with use of sunn hemp in the crop rotation and controlled traffic farming. Sugarcane production using controlled traffic farming allows an increased number of harvesters, with consequent reduction of 43% in greenhouse gases emissions, 24% in fossil depletion, and 44% in acidification potential when compared to burned cane scenario. These results reinforce that better agricultural management practices should be used to maximize number of cuts in the sugarcane cycle. (c) 2015 Society of Chemical Industry and John Wiley & Sons, Ltd
Keywords: sunn hemp; crotalaria; soybean; reduced tillage; controlled traffic farming